2020
DOI: 10.1111/1750-3841.15552
|View full text |Cite
|
Sign up to set email alerts
|

Food safety governance in Saudi Arabia: Challenges in control of imported food

Abstract: The operating environment for food safety interventions in nations such as Saudi Arabia, with limited local agricultural productivity, high reliance on foreign food imports and observance of Islamic laws, is remarkably challenging for the national control and regulatory institutions, since compliance to the mandatory food safety regulations and the local religious Halal standards must be ensured. This review offers a comprehensive analysis of the recently restructured food safety governance in Saudi Arabia fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Food safety has long been the subject of research worldwide, 19 , 20 and it is acknowledged to be an important national security issue. 21 During the COVID-19 era, a large number of studies have shown that virulence, individual susceptibility, and immunity are key determinants of susceptibility to disease following exposure to the COVID-19 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Food safety has long been the subject of research worldwide, 19 , 20 and it is acknowledged to be an important national security issue. 21 During the COVID-19 era, a large number of studies have shown that virulence, individual susceptibility, and immunity are key determinants of susceptibility to disease following exposure to the COVID-19 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these particular bacteria need treatment, and the most common type of treatment is antibiotics which recently became less effective toward them due to a highly resistant mechanism. Therefore, this paper will demonstrate some information about antibiotic treatment mechanisms, resistance mechanisms and some statistics about antibiotics resistance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Reporting an outbreak in Saudi Arabia has many challenges due to an ine cient data collection system (Al-Mazrous 2004). Therefore, since 2003, the Saudi Food and Drug Authority (SFDA) has acquired the control of all food safety regulations, which has also helped avoid any overlap with other Saudi Arabian authorities (Alrobaish et al 2021). Approximately 80% of the available food in Saudi Arabian markets is imported and 15.71% of these imported food products are meat-based (Alrobaish et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to import food products into Saudi Arabia, the SFDA mandates a registration certi cate authorised by the Saudi health ministry, an industry certi cate authorised by the commerce ministry, and a quality certi cate (e.g. International Organization for Standardization 9001 or 22000, Good Manufacturing Practice, and Hazard Analysis Critical Control Point)(Alrobaish et al 2021). Therefore, to ensure public safety, the SFDA has announced a list of countries from where the import of food into Saudi Arabia is prohibited (available at bit.ly/2TOoNMm)(Alrobaish et al 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation